Status Quo and Future Challenges for the Research Infrastructure in the Field of Culture - Jörg Rössel; Gunnar Otte (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The term "culture" is notorious for the multitude of its meanings. This expertise strictly focuses on culture in terms of the arts. We adopt a sociological as well as an economic perspective. Research questions are subdivided into three spheres of action: artistic production and its organization; the distribution and valuation of culture; and the consumption and reception of culture. The data requirements and the availability of adequate data vary substantively, depending on artistic branches (music, performing arts, etc.) and specific research questions. In order to make the empirical investigation of culture a flourishing field, we recommend the following improvements of the data infrastructure: firstly, comprehensive surveys of artists on the one hand and cultural consumption on the other hand should be carried out with the support of public funding; secondly, a national cultural statistic should be established, illuminating the size, impact and evolution of the cultural sector in comparative perspective; thirdly, the public availability of organization-level data as well as communal surveys on cultural production and consumption issues should be improved; fourthly, the transparency of existing data sources and their accessibility should be improved by archiving them centrally, e.g. at the ZA.
Keywords: 330; culture; arts; artists; production; distribution; consumption; reception; cultural sector; cultural industries.